Experimental drop test investigation into wetdeck slamming loads on a generic catamaran hullform. (1st May 2016) - Swidan, Ahmed; Thomas, Giles; Ranmuthugala, Dev; Amin, Walid; Penesis, Irene; Allen, Tom; Battley, Mark
Abstract: A series of drop-test experiments was performed to investigate the hydrodynamic loads experienced by a generic wave-piercer catamaran hullform during water impacts. The experiments, which focus on the characterisation of the unsteady slam loads on an arched wetdeck, were conducted using a Servo-hydraulic Slam Testing System (SSTS) that allows the model to enter the water at a range of constant speeds up to 10 m/s. The systematic and random uncertainties associated with the drop test results are quantified in detail. The relationships between water-entry velocity and both slam force and pressure distributions are presented and discussed with a strong relationship between the slam force peak magnitudes and impact velocity being observed. In addition the three dimensionality of the water flow in these slam impact events is characterised. Highlights: Comprehensive set of benchmarking data is provided for use in the validation of numerical techniques to predict slam impact loads of catamarans. New definition for the air gap elevation of catamarans is proposed. Strong relationship between the relative impact velocity and wetdeck slam force magnitude is concluded. Slamming pressure data along the highest points on the wetdeck arch is presented. Wetdeck slam is proven to be a three-dimensional phenomenon.